Comparison of two protocols for early treatment of dentoskeletal Class III malocclusion: Modified SEC III versus RME/FM. (30th November 2020) - Fabozzi, Filomena Federica; Nucci, Ludovica; Correra, Antonia; d'Apuzzo, Fabrizia; Franchi, Lorenzo; Perillo, Letizia
Abstract: Objective: To compare the short‐term cephalometric outcomes of the protocols modified splints, Class III elastics, chincup (SEC III) and rapid maxillary expansion and facial mask (RME/FM) for the early treatment of growing subjects with Class III dentoskeletal malocclusion. Settings and sample population: This retrospective observational study included 20 patients (11 males, nine females) treated with the modified SEC III protocol and 31 patients (16 males, 15 females) treated with the RME/FM one. The sample was evaluated before (T1, mean age 7.9 ± 1.0 years) and at the end of treatment (T2, mean age 9.0 ± 1.0 years). Statistical comparisons between the two groups were performed with independent sample t tests. Results: Both the modified SEC III and the RME/FM sample groups showed significantly favourable effects in terms of maxillary advancement (SNA +1.3° and +1.5°, respectively), control of mandibular projection (SNB −0.5° and −0.8°, respectively), and intermaxillary relationships (ANB +1.8° and +2.3°, respectively; Wits +3.4 and +1.9 mm, respectively). The modified SEC III group showed a statistically significant greater control in the intermaxillary divergency considering the SN to Pal. Pl. ( P  < 0.006) and Pal. Pl. to Mand. Pl. angle ( P  < 0.002) with a difference of 2.3 mm between the two groups. Limitations: The main limitations of this study are its retrospective nature and the short‐term outcomes. Conclusion: Early treatment of growing patients with dentoskeletal Class III disharmonies is efficient using either modified SEC III or RME/FM protocols. However, a higher vertical control is achieved with the modified SEC III.